VRIO Analysis to Measure E-Business Readiness in the Automotive Industry in East Java (Study on Otobus Company Kalisari and Otobus Company Menggala) - Nur Yudiono; Wilopo Wilopo; Mohammad Iqbal (Sekolah Pascasarjana Universitas Brawijaya, 2019)
The development of information technology especially e-business must be responded to by the company's internal environment in order to compete with competitors and survive the changes in the external environment. The resource-based approach, namely resource based view with VRIO analysis, is one tool to measure the ability of company resources to become a competitive advantage, the automotive industry as a part of the transportation industry must also be able to respond to changes in existing external environments such as electronic ticketing systems. it has been used by trains and airplanes. The results of the research at two autobus companies show that this company already has a sustainable competitive advantage and other companies do not have a sustainable competitive advantage, while in terms of readiness, the two companies are still not ready to implement e-business. In addition, the results of this study can only provide an overview of the readiness of the auto industry in using e-business, this is due to the nature of the company that is closed from research activities so that only two companies can be used as research objects.